Urinary bladder rupture secondary to obstructive urolithiasisin a Jamnapari goat - Tan, Y. K.; Khairuddin, Nurul Hayah; Hiew, Mark Wen Han; Radzi, Rozanaliza (Veterinary Association Malaysia, 2017)
This report describes the complications of obstructive urolithiasis in the lower urinary tract causing urinary bladder rupture in a Jamnapari buck. A 3-year-old Jamnapari buck was presented with the complaint of stranguria, subsequent anuria and a progressively distended abdomen for the past three days. Upon physical examination, body temperature, pulse rate and respiration rate were increased. Uroliths could be felt within the urethra in the ventral abdomen region. A urolith was removed via amputationof the urethral process, but the patency of the urethra could not be established. Transabdominal ultrasound revealed anechoic areas around the bladder, and the bladder was relatively small for a urinary obstructed goat. The bladder wall was thickened and shadow of sludge was observed within the bladder. Abdominocentesis was done and fluid analysis revealed that it was a haemorrhagic effusion. Blood results revealed renal disease, liver disease, muscle injury and haemoconcentration. Retrograde cystourethrogram revealed no urolithswithinthe urethra but there was leakage of the contrast agent from the bladder into the peritoneal cavity. The final diagnosis was complete blockage of the lower urinary tract leading to bladder rupture. Exploratory laparotomy was done and emergency cystorraphy was planned. Due to the poor condition of the urinary bladder with presence of septic peritonitis, the goat was euthanised.